Shaping the Health and Long-Term-Care Infrastructure Serving Older Adults: Historical Trends and Future Directions - Fralich, Julie (Maine Policy Review, 2015)
Over the last few decades, federal and state policy have been driving a shift away from nursing facility-based long term services and supports (LTSS) toward home and community-based services (HCBS). As Maine’s aging demographics generate increasing demand for LTSS, the state faces a number of significant challenges as it tries to make living at home longer a viable option for more and more older adults who need assistance in order to do so. This article reviews the confluence of demographic and policy shifts that will shape the future of Maine’s LTSS system.
Keywords: long term services and supports; Maine; home and community-based services; nursing homes; aging